The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/oby.21721
|View full text |Cite
|
Sign up to set email alerts
|

Brown adipose tissue does not seem to mediate metabolic adaptation to overfeeding in men

Abstract: Objective Brown adipose tissue (BAT) generates heat in response to cold, and low BAT activity has been linked to obesity. However, recent studies are inconclusive as to whether BAT is involved in diet-induced thermogenesis and mitigates weight gain from prolonged overeating. We therefore investigated whether BAT activity is related to metabolic adaptation arising from 8 weeks of overfeeding in humans. Methods Fourteen men (aged 24±3 years, BMI 24.5±1.6 kg/m2) were overfed by 40% for 8 weeks. Before and after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 21 publications
0
32
1
Order By: Relevance
“…However, recent data in humans indicate that unlike CIT, DIT is probably not mediated by BAT [26]. Additionally, we recently reported that BAT probably does not mediate the metabolic adaptation following 8 weeks of overfeeding in men [27]. Together, these studies do not support a role of BAT in modulating DIT and do not lend support to an important role for BAT in the regulation of human body weight as previously suggested by Kozak [28].…”
Section: Bat Activation Vs Bat Inductionmentioning
confidence: 68%
“…However, recent data in humans indicate that unlike CIT, DIT is probably not mediated by BAT [26]. Additionally, we recently reported that BAT probably does not mediate the metabolic adaptation following 8 weeks of overfeeding in men [27]. Together, these studies do not support a role of BAT in modulating DIT and do not lend support to an important role for BAT in the regulation of human body weight as previously suggested by Kozak [28].…”
Section: Bat Activation Vs Bat Inductionmentioning
confidence: 68%
“…The first study to use IRT to estimate SST was performed in 2011 . Ten studies were then published between 2011 and 2016 , six in 2017 , six in 2018 , and one until April 2019 .…”
Section: Resultsmentioning
confidence: 99%
“…Most, but not all, of the identified studies ( n = 18; 75%) included cooling protocols, although the duration, temperature, and the way of inducing cooling differed between studies (Figure ). Nine out of these eighteen studies used hands/feet immersion in cold water (temperature 10.8°C ± 8.7°C, duration: 6.1 ± 6.8 minutes) . Seven of these nine studies used a cold exposure of < 5 minutes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first study dedicated to determination of a contribution of BAT to adaptive DIT was published recently by Peterson et al . . In their study involving 8 weeks overfeeding by 40% of weight maintenance energy intake in healthy males, sleeping energy expenditure was increased by 4.7% above that expected based on the amount of weight gained.…”
Section: Brown Adipose Tissue Adaptive Thermogenesismentioning
confidence: 94%